Public Infrastructure Spending and Economic Growth in Nigeria: An Error Correction Mechanism (ECM) Approach - Ekpung, Edame Greg (Journal of Social Economics Research, 2014)
The aim of this study is to critically analyze the determinants of public infrastructure spending and economic growth in Nigeria, using available time series data from 1970 to 2010. The specific objective of the study with an overriding aim of providing policy-relevant evidence are: to examine the trend in public expenditure on infrastructure in Nigeria between 1970 to 2010; to compare the trend in public expenditure between the military and democratic government in Nigeria between 1970 to 2010; to determine the relationship between expenditure on infrastructure and long-run economic growth; ascertain the factors that influence public expenditure growth in infrastructure; test for the stability of growth in public expenditure on infrastructure over time and derive policy recommendations based on the findings of the study. The model specification is based on the Ordinary Least Squares (OLS) multiple regression. While the estimation procedures is that of the Johansen Maximum Likelihood (JML) and OLS estimators.